Effect of different sugar concentration on the rheological and textural properties of fish mince - Ashari, Rozzamri (Malaysian Society of Agricultural Engineers, 2019)
Fish mince were prepared from Alaska Pollock where fish were headed, gutted, washed and minced. The fish mince were subjected to three formulations with different types of sugar which was sucrose, sorbitol and mannitol at 4%, 6% and 8% (w/w) concentration. Rheological properties and textural properties of the fish mince is determined using a rheometer and texture analyser. Rheological properties showed that as the sugar concentration increases, the fish mince displayed more elastic properties rather than viscous. Higher stress and force were needed for deformation of fish mince at higher sugar concentration. Fish mince added with mannitol at 8% (w/w) displayed the highest value of G’ and G’’. Textural properties also concur with rheological results as it shows that an increase in sugar concentration, increases the gelling strength of the fish mince especially with mannitol (p<0.05). An increase from 4% to 6% concentration of sugar showed a significant difference for all sample (p<0.05). However, sucrose and sorbitol does not display any significant difference with an increase from 6% to 8% (p>0.05). This indicates that a lower sugar concentration could be used to produce similar gelling strength of higher sugar concentration.